PENINGKATAN PENGETAHUAN ANAK SD MELALUI EDUKASI GIZI TENTANG MAKANAN JAJANAN SEHAT DAN GIZI SEIMBANG DENGAN MEDIA BUKU CERITA BERGAMBAR DI SD TIYARAN 01 DAN 03 SUKOHARJO - purwani, eni (WARTA, 2016)
There are so many snack that sold at the school that has a high risk for the health. Range from snak that consume by student have a potential occur the contamination biology or chemical that disturb the health according the long term or the short term. In generally, the seller of the snack didnât know the food safety that they sold. And so do the student at Tiyaran 1 and 3 Elementary School didnât really know about the healthy snack. This activity is promotif and preventif efforts, so the student can know and understanding the healthy snack in the school also can do the protection toward dangerous food material. The methode that use for this activity is giving education through the media Pictorial Story Book that has content about things that concern the snack at the school that created in the form pictorial story that simple and interesting. The purpose using media pictorial story book is to be the participant to easy undertanding the material. Beside that do the demonstration test the dangerous substance that consist of Formalin test, Borax, and the food colour that dangerous such as Methanil Yellow and Rhodamin B. This education activity can improve the elementary studentâs knowledge, teacherâs, and canteen organizerâs about the healthy snack. Beside that, also improve the knowledge about the dangerous material with test the snack at the school with reagen test to detect the existency of formalin, borax, methanil yellow, rhodamin B.